THE INFLUENCE OF REWARDS AND PUNISHMENT ON EMPLOYEE PERFORMANCE AT PT. PLN ULP PALOPO CITY - Purwadi, Tri; Rahyuni, Kadek Elvy; Danayasa, Gede Agus; Putri, Tria Manda; Nugraha, Yuda Satria (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2024)
This research aims to determine and analyze the influence of rewards and punishment on employee performance at PT PLN ULP Palopo City. The type of research carried out is quantitative. The type of data used comes from primary data and secondary data. Data collection was carried out by means of observation, interviews and questionnaires. Data analysis using Multiple Linear Regression. The research results show that simultaneously Reward and Punishment have a significant effect on employee performance. Meanwhile, partially rewards and punishments do not have a significant effect on employee performance.